Impact of sink location on hand hygiene compliance after care of patients with Clostridium difficile infection: a cross-sectional study - Deyneko, Alexander (BMC Infect Dis, 2016)
BACKGROUND: The impact of sink location on hand washing compliance after contact with patients with Clostridium difficile infection (CDI) is poorly understood. The aim of this study is to determine the location of hand wash sinks available to healthcare workers (HCWs) after caring for patients with CDI and to assess the impact on hand washing compliance. METHODS: We performed a cross-sectional study in a 637-bed tertiary care hospital, Canada. HCW hand hygiene compliance after contact with CDI patients was measured through direct unobtrusive observations. Location of sinks in relation with the patients’ rooms was assessed on the day of diagnosis. Predictors of compliance were assessed through univariate and multivariate logistic regression. RESULTS: 247 hand hygiene opportunities following care of a CDI patient were observed. Glove use compliance was 85.4 % (211/247), but hand washing compliance after care of CDI patients was only 14.2 % (35/247). Hand rubbing was performed instead of hand washing in 33.2 % of opportunities (82/247). The median distance between the patient zone of CDI patients and the nearest sink was 13.1 m (interquartile range, 7.6-23.2). Sinks were directly visible upon exiting the patient’s room on only 33.2 % (82/247) occasions. By multivariate analysis, an increasing distance between the patient zone and the nearest sink was inversely associated with hand washing compliance (adjusted OR, 0.90, 95 % CI, 0.84-0.97; P = 0.008), while proper timing of glove removal upon leaving the patient zone was directly associated with hand washing compliance (adjusted OR, 14.87; 95 % CI, 1.93-114.43; P = 0.01). CONCLUSIONS: Hand washing compliance following contact with patients with C. difficile infections was low. Poor access to sinks is associated with decreased hand washing compliance. Improvement strategies are urgently needed.